2020
DOI: 10.1002/path.5418
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinase fusions act as a significant alternative driver of the serrated pathway in colorectal cancer development

Abstract: Serrated polyps are a clinically and molecularly heterogeneous group of lesions that can contribute to the development of colorectal cancers (CRCs). However, the molecular mechanism underlying the development of serrated lesions is still not well understood. Here, we combined multiple approaches to analyze the genetic alterations in 86 colorectal adenomas (including 35 sessile serrated lesions, 15 traditional adenomas, and 36 conventional adenomatous polyps). We also investigated the in vitro and in vivo oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…In line with previous studies, our findings recognized BRAF V600E or KRAS mutations as the triggering event of the serrated pathway ( 27 ). The overall rate of BRAF V600E (53/90, 59%) was within the range reported in the existing literatures from 50% to 83% ( 28 , 29 ). The high level of mutant BRAF in SPs is becoming growingly relevant as a poor prognostic factor ( 30 ).…”
Section: Discussionsupporting
confidence: 84%
“…In line with previous studies, our findings recognized BRAF V600E or KRAS mutations as the triggering event of the serrated pathway ( 27 ). The overall rate of BRAF V600E (53/90, 59%) was within the range reported in the existing literatures from 50% to 83% ( 28 , 29 ). The high level of mutant BRAF in SPs is becoming growingly relevant as a poor prognostic factor ( 30 ).…”
Section: Discussionsupporting
confidence: 84%
“…15,17,18 Interestingly, a recent study showed that a subset of sessile serrated lesions harbor RTK fusions. 19 Although no NTRK fusions were identified in this study, the high frequency of MMR deficiency in RTK fusionpositive colorectal cancers might imply their relationship to the serrated pathway of tumorigenesis.…”
Section: Discussionmentioning
confidence: 71%
“…According to data from Western countries including the United States, Canada, Australia, Germany, Austria, and Switzerland, frequencies of BRAF V600E mutations in SSLs range from 63% to 100% ( Supplementary Table S1) [22,24,[33][34][35][36][37][38][39][40][41]. However, in East Asian countries, including South Korea, Japan, and China, BRAF mutation frequencies in SSLs have been reported to be relatively lower, ranging from 14% to 86% (Supplementary Table S1) [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Using these data, we conducted a pooled analysis to directly compare the frequencies of BRAF mutations in SSLs between Western and Eastern countries (Table 2).…”
Section: Molecular Pathogenesis Of Sslsmentioning
confidence: 99%